Thailand’s Experience of Developing Special Border Economic Zones and Some Policy Implications for Vietnam in Developing Border Economic Zones - Minh, Nguyen Tien; Hoi, Ha Van (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 4, 2019)
Thailand is one of the first countries in South East Asia establishing the proposed Special Border Economic Zone with Malaysia, Myanmar, Laos, and Cambodia. However, Thai government has to adjust development strategy after 5 years. This research clarifies the purposes, process, and Thailand’s SBEZ model before the strategic adjustment, and simultaneously, offers a comparison with Vietnam’s BEZ in order to suggest policies for developing Vietnam’s BEZ in the future.